A Correlation Between the Function of Controlling and the Process of Risk Management in the Company - Živkov, Emil; Nerandžić, Branislav; Kuzmanović, Bogdan (International Journal of Industrial Engineering and Management, 2015)
It is highly important to identify the right place for implementing the key role of coordinating the overall process of risk management in an organization. In addition to the right place it is important to determine the right time for it. The entire course of risk management activities must be integrated with the process of management of goals of the organization. If we take into account that for the synchronization of the management organization of company goals, the most responsible factor, somehow, is the controlling function due to its very nature of activity, then a logical conclusion is being imposed that this function is also the most suitable one for identifying the place of coordination of the risk management process. And not only as an organizational unit and according to the nature of its tasks, but also of the time synchronization through activities of planning and reporting, in view of the impact analysis, estimated and actual, transferred and avoided business risks. Article history: Received (20.10.2015); Revised (30.11.2015); Accepted (11.12.2015)